An analysis of skills training for inmates in prison workshops: the case of Harare central prison workshops from 2008-2015. - Bambire, Precious (Midlands State University, 2018)
The overall aim of the study was to shed light on the main reasons behind skills training of inmates in prison workshops with specific reference to Harare prison workshops as it is the biggest among all prison workshops in Zimbabwe and it offers a lot more programs when it comes to the rehabilitation of the offender. The study was triggered by the need to shed light on the importance of the skills’ training initiative for those in custody as it is part of the rehabilitation programs and its usefulness towards the reduction of idleness and recidivism. The program is meant to ensure that the offenders upon release from prison become self reliant. The study employed both qualitative and quantitative methods of data collection. A sample of 22 respondents was selected from a targeted population of 50 participants. The sample included 14 inmates, 6 officers and other 2 officers as the key informants. The key informant interviews which were conducted with the prison officers were of great use as they allowed one on one asking of questions from the people who are directly responsible for tutoring the inmates at the workshops and are familiar with them. Questionnaires were thematically analyzed in order to obtain an accurate description and understanding of the respondents’ lived experiences with regard to skills training and its benefits. The respondents cited how they are looking forward to utilize the acquired skills either by self employment or forming of cooperatives so that they avoid re-offending. This was because they committed crimes in the first place due to unemployment as there was need to take care of their families. Therefore from the study it was concluded that the organization together with the government should work hand in hand towards putting in place measures to source funds so that inmates are given starter packs to start their own projects after release from prison. The major challenge of the study was that a small sample was used and all participants were drawn from one institution which may however compromise the significance of this study. This was a result of the bureaucratic and security policies of the organization that restricts civilians from being in direct contact with the inmates, hence a few inmates were recommended. Future research in this area should use a larger sample to ensure greater significance.